Snow White with the red hair. 12 - Akiduki, Sorata (Shojo beat manga., 2021)
"Shirayuki is an herbalist with naturally bright-red hair, and the prince of Tanbarun wants her all to himself! She's rescued from her plight by Zen, a prince from the neighboring kingdom ... As news of Izana's impending coronation spreads, people from all over travel to the capital city of Wistal. During the preparations, Zen asks Shirayuki to play host to Prince Raj of Tanbarun, sending shock waves through the palace. To think that a common court herbalist would be entrusted with such a task! But that's not the only change coronation day brings."--Provided by publisher